Research on the Attenuation Characteristics of AE Signals of Marble and Granite Stone - Haiyan Wang; Ji Ma; Feng Du; Gongda Wang; Quan Zhang; Xiaoshen Li (Advances in Civil Engineering)
When an underground rock is deformed or fractured by an external or internal force, the energy will be released in the form of an elastic wave, which is known as the acoustic emission (AE) phenomenon. Extracting useful information from complex AE signals for the early warning of fracture characteristics and the damage monitoring of rock materials is of great significance for the prevention and control of dynamic disasters in coal mines. In this work, by taking rod-shaped rocks and plate-shaped rocks with different lithologies as the research objects, the elastic wave propagation characteristics of the rod-shaped rocks and plate-shaped rocks were studied by a self-constructed experimental platform. The results demonstrate that the elastic wave attenuation of the rod-shaped marble was the fastest, and the elastic wave attenuation characteristics of the three groups of rod-shaped granite were similar. The attenuation of the P-wave preceded that of the S-wave. With the increase in the propagation distance, the amplitude of the large-scale plate-shaped rock showed an approximate exponential attenuation characteristic. The elastic wave attenuation of the plate-shaped granite in the 0° direction was stronger than that of the plate-shaped marble, and it was weaker than that of the plate-shaped marble in the 45° and 90° directions. The energy changes in marble were more severe than those in granite. The main dominant energy of the AE signals of experimental rock was concentrated in the range of 0–176.78 kHz, and part of the residual energy was located in the high-frequency band of 282.25–352.56 kHz.